ENCOURAGING AND LIMITING INVESTMENT FACTORS - Aničić, Jugoslav; Petrović, Vesna; Simić, Nataša; Aničić, Dušan (Journal of process management and new technologies, 2020)
Investments are the basis for the growth and development of a company and for improving its competitiveness in the regional and international markets. Investment carries with it uncertainty and a high degree of risk since it is usually a long period of time from the moment of investment to the effects of return on investment. Therefore, an appropriate analysis of investment projects is required based on an assessment of the company's development capabilities. A number of factors, both internal and external, influence the successful realization of investment investments. Many of them cannot be operated by the company, and many other, unforeseen factors are emerging in a dynamic economic environment that can decisively affect the future business and survival of the company.
Keywords: investments, strategy, investment factors, company